Acetabular Fracture: Retrospective Analysis of Thirty Three Consecutive Cases with Operative Management - Shrestha, D; Dhoju, D; Shrestha, R; Sharma, V (Kathmandu University Medical Journal, 2015)
Background With the development of better imaging modalities including 3D CT scan and availability of technical expertise, operative management is increasingly performed for acetabular fracture but many patients in developing countries like Nepal, are still being treated with prolonged skeletal traction. Objective To analyses epidemiology, types of acetabular fracture and functional and radiological outcome of patients with acetabular fracture treated with open reduction and internal fixation (ORIF). Method Inpatients hospital records of patients treated with ORIF in between June 2007 to June 2014 were evaluated. Patient’s demographic data, mode of injury, injury hospital interval, injury surgery interval, associated injuries, surgical approach, total hospital stay and peri and post-operative complications were recorded and radiological and functional outcomes were evaluated. Result Thirty three patients (Male: 24 Female: 9) with average age 39 years (range: 21 to 65 years) were operated for acetabular fracture. Twenty one patients (63%) had injury related with motor vehicle accidents and nine (24%) of them had motorbike accidents. Injury hospital interval ranges from 7 to 36 days. Average injury-surgery interval was 21 days and average hospital stay was 22 days. Bicolumnar fractures were found in 15. Nine patients had dislocation of hip and 15 had concomitant other injuries. Biculumanr fixation was performed in 15 patients, posterior column and or wall in nine with Kocher Langenbeck approach and anterior column and or wall in other nine with ilio-inguinal approach. Radiological reduction was anatomical in 18; excellent/good functional outcome was in 26 and radiological outcomes were excellent in 14. Three patients had developed Hypertopic ossification. Follow up period ranged from 6 to 48 months and 15 patients (45%) had follow up >2 years. Conclusion Acetabular fractur can be effectively managed with ORIF and have predictable and comparable functional and radiographic outcomes. Upgrading the existing facilities and training of orthopedic surgeon for acetabular fracture management is important to shorten injury-surgery interval due to lack of such facilities. Kathmandu University Medical Journal Vol.12(4) 2014; 279-287